THE EFFECTS OF CULTURAL DIMENSIONS ON SERVICE QUALITY, CUSTOMER ENGAGEMENT, CUSTOMER SATISFACTION AND CUSTOMER LOYALTY IN MULTI-NATIONAL AIRLINE SECTORS - SRIBOONLUE, Umawasee (Asian Administration and Management Review, 2022)
Current business landscape and dynamism of the business environment have increased competitiveness in service industry. Also, understanding cultural differences intervening in customer decision is crucial for this global era. Therefore, multi-national airline sectors must now pay greater attention to customer need by exploring ways to improve customer engagement, satisfaction, and loyalty through their services quality. Toward this end, the purposes of this research were to study the effects of cultural dimensions consisting of power distance, individualism, masculinity, uncertainty avoidance, and long-term orientation on service quality, customer engagement, customer satisfaction, and customer loyalty in multi-national airline sectors. The research methodology was quantitative research with survey method by using questionnaires for data collection. The respondents were 800 of Thai and foreign passengers who have been participated in multinational full-service airlines during the last three years. Due to hypothesis testing, inferential statistics used were Pearson’s Product Moment Correlation Coefficient and Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicated that cultural dimensions had positive effects on service quality, and service quality mediated the effects of cultural dimensions on customer engagement, customer satisfaction, and customer loyalty at a significance level of 0.001. Besides, customer engagement had effects on customer satisfaction and customer loyalty, and customer satisfaction had a positive effect on customer loyalty at a significance level of 0.001.